The Survey of Use and Ownership Rights in Finnmark – A Change of Direction? - Ravna, Øyvind (International Journal on Minority and Group Rights, 2021)
In 2008, the Finnmark Act initiated a process of surveying land rights the Sámi and others may have in Finnmark, the core Sámi area of Norway. The Finnmark Commission, which was established to conduct the survey has completed six investigations. The assessments and conclusions in the first five reports are so similar in terms of collective rights appears as cut from the same cloth. In December 2019, the Commission presented its sixth report, which covers the municipality of Karasjok, a community with a Sámi majority. This report marks a significant change from the previous ones, as the Commission for the first time concludes that the people in an investigation field own their outlying areas. This article examines how the Commission arrived at that result, pointing out that it is more an outcome of a different approach to the legal history and international law, than substantive differences in factual circumstances.